Analisis Bibliometrik Promosi Kesehatan Selama Masa Pandemi COVID-19 Menggunakan VOSviewer - Rohmayanti Rohmayanti; Retna Tri Astuti (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT  This study aims to analyze trends in the scope of research on health promotion during the COVID-19 pandemic. The method used is a bibliometric review process: article searches through Harzing's Publish or Perish, and from the Google Scholar database, data mapping is then carried out using VOSviewer. The results showed that the number of publications on search results regarding health promotion via Google Scholar during the COVID-19 pandemic in 2020–2022 was 18 articles involving 12 countries. Five articles were published in 2020, 11 articles were published in 2021, and 2 articles appeared in early 2022. A search with the keyword "Health Promotion During COVID-19" based on the topic area with titles, keywords, and abstracts resulted in 18 relevant articles. The most citations were made by Zan Gao, with a total of 62. Based on the results of analysis and mapping with VOSviewer on network visualization, it is known that the keyword that appears the most is “pandemic" or COVID. The results of the overlay visualization found that the keywords pandemic and COVID are connected with several other terms in three clusters. The most published articles found in 2021 were 11 articles. In the density visualization, it is known that the most commonly used keywords are pandemic and COVID, which have strong links to health and health promotion. In contrast, the keywords still few are individual, mental health, child, impact, spring, risk, and support. The conclusion of this study is in the form of research trends on health promotion during the COVID-19 pandemic, namely research with the keywords pandemic, COVID, health, and health promotion. The novelty for further research related to health promotion is research related to the keywords individual, mental health, child, impact, spring, risk, and support.   ABSTRAK Tujuan penelitian ini untuk menganalisa tren ruang lingkup penelitian tentang promosi kesehatan selama pandemi COVID-19. Metode yang digunakan menggunakan proses kajian bibliometrik, penelusuran artikel melalui Harzing’s Publish or Perish, dan dari database Google Scholar kemudian dilakukan pemetaan data menggunakan VOSviewer. Hasil penelitian menunjukkan bahwa jumlah publikasi hasil pencarian mengenai promosi kesehatan melalui Google Scholar pada masa pandemi COVID-19 di tahun 2020-2022 sebanyak 18 artikel yang melibatkan 12 negara. Publikasi tahun 2020 sebanyak 5 artikel, tahun 2021 meningkat 11 artikel dan awal tahun 2022 sejumlah 2 artikel. Pencarian dengan kata kunci “Health Promotion During COVID-19” yang didasarkan pada area topik dengan judul, kata kunci, dan abstrak diperoleh 18 artikel yang relevan. Sitasi terbanyak didapatkan oleh Zan Gao dengan jumlah 62. Berdasarkan hasil analisis dan pemetaan dengan VOSviewer pada visualisasi jaringan diketahui bahwa kata kunci yang paling banyak muncul adalah pandemic, COVID. Hasil visualisasi overlay menemukan kata kunci pandemic, COVID terhubung dengan beberapa istilah lain dalam 3 klaster. Publikasi artikel terbanyak ditemukan pada tahun 2021 sebanyak 11 artikel. Pada visualisasi densitas diketahui bahwa kata kunci yang paling umum digunakan adalah pandemic dan COVID yang memiliki tautan kuat ke health dan health promotion, sedangkan kata kunci yang masih sedikit yaitu individual, mental health, child, impact, spring, risk, support. Kesimpulan penelitian ini berupa tren penelitian tentang promosi kesehatan pada masa pandemi COVID-19 yaitu penelitian dengan kata kunci pandemi, COVID, health dan health promotion, sedangkan kebaruan untuk penelitian terkait health promotion selanjutnya adalah penelitian yang dihubungkan dengan kata kunci individual, mental health, child, impact, spring, risk, support.